2018
DOI: 10.1111/1471-0528.15500
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year follow up of a low glycaemic index dietary randomised controlled trial in pregnancy—no long‐term maternal effects of a dietary intervention

Abstract: Objective To determine whether a dietary intervention in pregnancy had a lasting effect on maternal outcomes of diet, HbA1c and weight retention 5 years post‐intervention; and to establish whether modifiable maternal behaviours were associated with these outcomes. Design Randomised control trial of low glycaemic index (GI) diet in pregnancy with longitudinal follow up to 5 years post‐intervention. Setting Dublin, Ireland (2007–2016). Population In all, 403 women of 759 (53.1%) were followed up at 5 years. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
(70 reference statements)
2
13
0
Order By: Relevance
“…Similar findings were described for other maternal characteristics within the ROLO cohort, investigated elsewhere. 4 This finding also suggests that although the ROLO study had positive effects of GWG, this did not have a lasting impact on BP, as suggested in previous research. 26 Body mass index at early pregnancy and weight at the 5-year follow-up were associated with HTN stage 1 at the 5-year follow-up.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar findings were described for other maternal characteristics within the ROLO cohort, investigated elsewhere. 4 This finding also suggests that although the ROLO study had positive effects of GWG, this did not have a lasting impact on BP, as suggested in previous research. 26 Body mass index at early pregnancy and weight at the 5-year follow-up were associated with HTN stage 1 at the 5-year follow-up.…”
Section: Discussionsupporting
confidence: 69%
“…This nonsignificant finding could be explained by these women already being identified as high risk for future HTN and thus managed with pharmacological treatment. Similar findings were described for other maternal characteristics within the ROLO cohort, investigated elsewhere 4. Although SBP and DBP are routinely measured in pregnancy, MAP is rarely calculated in clinical practice 24.…”
supporting
confidence: 79%
“…A small benefit was found on maternal insulin levels early in pregnancy only, however, no effect was found for leptin or markers of inflammation. Follow-up data from the ROLO trial during the first six months and five-years postpartum found a limited sustained intervention effect [37][38][39] . Greater weight loss was found at three months postpartum, however, this difference was not detected at six months or five years postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial email invitation, stakeholder‐specific information will be included outlining the project background, the Delphi purpose and process, and the potential impact of their participation on nutrition research within this population group . The survey will be disseminated using DelphiManager ™ software (developed by the COMET initiative) .…”
Section: Methodsmentioning
confidence: 99%
“…Maternal nutrition during pregnancy can affect maternal health during pregnancy and beyond . It also influences the intrauterine environment of the developing fetus and this may influence the health and development of children in utero right through to adulthood . Therefore, nutrition during pregnancy is an important consideration in the management of pregnant women and in the overall life course approach to health care and health promotion.…”
Section: Introductionmentioning
confidence: 99%